Youth disengagement: what's CARE got to do with it? - Dobler, Samantha (My University, 2017)
Do youth who disengage from society find their way into the criminal justice system or does the criminal justice system lead youth to disengage from society? This paper aims to contribute a student’s perspective on the (dis)engagement debate. In other words, to dispel the myth that “disengaged youth” just don’t care. Drawing on a critical, youth justice perspective, I conceptualize youth engagement, examine the bridges and barriers contributing to social inclusion/exclusion. I develop a CARE model for increasing access for youth. I pose practical questions concerning social support availability and opportunities for young people to contribute in meaningful ways to their community.
Presented on April 24, 2017 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: youth; criminal justice system